Early multicenter experience of Melody valve implantation in India - Kshitij Sheth; Sushil Azad; Bharat Dalvi; Maulik Parekh; Pramod Sagar; Rajaram Anantharaman; Sitaraman Radhakrishnan; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2021)
Background : Transcatheter valves provide a safe and effective alternative to surgery for treating dysfunctional right ventricular outflow tracts (RVOTs). We present our early multicenter experience of percutaneous pulmonary valve implantation (PPVI) using Melody valve (Medtronic Inc., Minneapolis, MN). Methods : Patients with stenosed conduits or degenerated bioprosthetic valves in RVOT with combined stenosis and regurgitation were evaluated for suitability of Melody valve implantation. After undergoing an initial structured training, PPVI using Melody transcatheter pulmonary valve (TPV) was guided by an approved proctor. Conduits were serially dilated and prestented with careful coronary interrogation, and bioprosthetic valves were dilated with high-pressure balloons. Clinical and echocardiographic follow-up was performed at 6 monthly intervals. Results : Fifteen patients (three females) aged 23.1 ± 9.5 years in NYHA Class II-III underwent Melody TPV implantation in four Indian centers. The underlying anatomy comprised surgically implanted bioprosthetic valves for pulmonary regurgitation (n= 5), conduit repair for pulmonary atresia (n = 4), Rastelli repair (n = 3), truncus (n = 1), and Ross procedure (n = 2). Twelve patients had more than one previous surgery. Doppler gradient decreased from 74.2 ± 21.5 mmHg to 10.2 ± 4.5 mmHg after the PPVI. At a median follow-up of 14 months (1-39 months), all the patients were in NYHA Class I with echocardiographic gradients of 8 ± 5.7 mmHg with no evidence of pulmonary regurgitation. There were no major procedural adverse events or deaths. Conclusions : Our early experience shows encouraging results of the PPVI program in India with proctored case selection and meticulous planning. It also confirms the safety and efficacy of Melody TPV for treating dysfunctional RVOT in postoperative patients.